A miniaturized and highly sensitive microwave sensor based on CSRR for characterization of liquid materials - Zakaria, Zahriladha; Abd Rahman, Norhanani; Mohd Ibrahim, Imran; Al Gburi, Ahmed Jamal Abdullah; Althuwayb, Ayman Abdulhadi; Saeidi, Tale; Dayo, Zaheer Ahmed; Ahmad, Sarosh (MDPI, 2023)
In this work, a miniaturized and highly sensitive microwave sensor based on a complementary split-ring resonator (CSRR) is proposed for the detection of liquid materials. The modeled sensor was designed based on the CSRR structure with triple rings (TRs) and a curve feed for improved measurement sensitivity. The designed sensor oscillates at a single frequency of 2.5 GHz, which is simulated using an Ansys HFSS simulator. The electromagnetic simulation explains the basis of the mode resonance of all two-port resonators. Five variations of the liquid media under tests (MUTs) are simulated and measured. These liquid MUTs are as follows: without a sample (without a tube), air (empty tube), ethanol, methanol, and distilled water (DI). A detailed sensitivity calculation is performed for the resonance band at 2.5 GHz. The MUTs mechanism is performed with a polypropylene tube (PP). The samples of dielectric material are filled into PP tube channels and loaded into the CSRR center hole; the E-fields around the sensor affect the relationship with the liquid MUTs, resulting in a high Q-factor value. The final sensor has a Q-factor value and sensitivity of 520 and 7.032 (MHz)/εr) at 2.5 GHz, respectively. Due to the high sensitivity of the presented sensor for characterizing various liquid penetrations, the sensor is also of interest for accurate estimations of solute concentrations in liquid media. Finally, the relationship between the permittivity and Q-factor value at the resonant frequency is derived and investigated. These given results make the presented resonator ideal for the characterization of liquid materials